PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS SOSIAL PROVINSI KALIMANTAN TIMUR - M. Zamroji Almursyid (CV. Adiba Aisha Amira, 2024)
Every company or institution has various goals to achieve. This goal can be achieved by utilizing existing resources. Even though there are various important resources in an agency, the factor that shows an institution's competitive advantage is its human resources. As currently faced with globalization and various changes in work regulations, human resources play a very important role in an institution. The success or failure of a previously determined service from a government agency depends greatly on the ability of human resources (employees) to carry out the tasks assigned. If the individuals in the agency, namely HR, can run effectively, the company will still run effectively. In other words, the continuity of success is determined by the performance of the employees. This research uses quantitative research methods. Quantitative research is research carried out by collecting data in the form of numbers. Quantitative research is a research method based on the philosophy of positivism, used to research certain populations or samples. Based on the two opinions above, it can be concluded that quantitative research is collecting data in the form of numbers that are used to research certain samples. Based on the results of the research and discussion carried out, it can be concluded as follows 1. Simultaneously, it can be concluded that the work environment and work discipline as well as organizational communication have a positive and significant influence simultaneously on employee work productivity 2. Partially, it can be concluded that the work environment has a positive and significant influence on employee work productivity 3. Partially, it can be concluded that work discipline has a positive and significant influence on employee work productivity in 4. Partially, it can be concluded that organizational communication has a positive and significant influence on employee work productivity